Correlator implementation for orthogonal CSS used in an ultrasonic LPS - Peréz Rubio, M. Carmen (2012)
This paper presents a new architecture for the correlation of orthogonal complementary sets of sequences (OCSS) and their performance in an ultrasonic local positioning system (U-LPS). OCSS are sets of sequences whose addition of correlation functions has ideal properties, that makes interference-free code-division multiple access (CDMA) possible. They can be used to encode the signals emitted by a CDMA based U-LPS, enhancing the performance of such systems in terms of immunity against noise, multipath propagation, and near-far effect. Also, the orthogonality of the codes offers an operation resistance to multiaccess interference, which endows the U-LPS with the capability of simultaneous emission from different beacons. On the other hand, the detection of OCSS codes can be performed by means of efficient algorithms. This paper presents an optimization of previous proposals allowing the simultaneous correlation of OCSS by using fewer operations and memory elements. Furthermore, the hardware implementation of the proposed optimization is also addressed, and an U-LPS based on this proposal is presented.